Reduced Energy Metabolism Impairs T Cell-Dependent B Cell Responses in Patients With Advanced HBV-Related Cirrhosis - Huang, Chunhong; Shao, Junwei; Lou, Congcong; Wu, Fengtian; Ge, Tiantian; Gao, Hainv; Zheng, Xiaoping; Dong, Xuejun; Xu, Lichen; Chen, Zhi (Frontiers in Immunology, 2021)
Background & Aims Patients with decompensated HBV-related liver cirrhosis (HBV D-LC) showed compromised immune responses, which manifested as a proneness to develop infections and hyporesponsiveness to vaccines，resulting in accelerated disease progression. The alterations in T cell-dependent B cell responses in this pathophysiological process were not well understood. This study aimed to investigate T cell-dependent B cell responses in this process and discuss the mechanism from the perspective of metabolism. Methods Changes in phenotypes and subsets of peripheral B cells between HBV D-LC patients and healthy controls (HCs) were compared by flow cytometry. Isolated B cells were activated by coculture with circulating T follicular (cTfh) cells. After coculture, the frequencies of plasmablasts and plasma cells and immunoglobin levels were analyzed. Oxidative phosphorylation (OXPHOS) and glycolysis were analyzed by a Seahorse analyzer. Mitochondrial function and the AKT/mTOR pathway were analyzed by flow cytometry. Results The proliferation and differentiation capacities of B cells after T cell stimulation were impaired in D-LC. Furthermore, we found that B cells from D-LC patients showed reductions in OXPHOS and glycolysis after activation, which may result from reduced glucose uptake, mitochondrial dysfunction and attenuated activation of the AKT/mTOR pathway. Conclusions B cells from HBV D-LC patients showed dysfunctional energy metabolism after T cell-dependent activation. Understanding the regulations of B cell metabolic pathway and their changes may provide a new direction to rescue B cell hyporesponsiveness in patients with HBV D-LC, preventing these patients be infected and improving sensitivity to vaccines.